THE GROWTH KINETICS OF Bacillus sp. D2.2 AT DIFFERENT pH AND SALINITY - Esti Harpeni; Supono Supono; Dwi Risca Septiani (Jurusan Perikanan dan Kelautan, 2018)
Isolate D2.2 is a bacterial isolate with 97% homology level with Bacillus sp. This isolate is a biocontrol bacterium capable of inhibiting the growth of Gram positive bacteria and Gram negative bacteria. The use of biocontrol bacteria is one solution of disease problem in cultivation organism. Prior to being applied to the field, D2.2 isolates need to go through a series of tests, one of which is growth kinetics testing under various environmental conditions, such as different degrees of pH and salinity. This is because environmental factors can affect the rapid growth of bacteria. The purpose of this study was to study the bacterial growth kinetics of D2.2 at different pH and salinity. The growth kinetics was observed by measuring optical density (OD) through a method of turbidimetry using a spectrophotometer at a wavelength of 625 nm to the stage of death. The results showed that the fastest growth rate was found at 20 ppt salinity with 0.179 h-1 and generation time of 5,588 hours. While in all pH treatments, generation time and growth rates achieved all treatments have the same pattern.